AUTHORSHIP PATTERN AND COLLABORATIVE RESEARCH IN THE FIELD OF ZOOLOGY - Vimala, V.; Pulla Reddy, V.; Vimala, V.; Pulla Reddy, V. (Malaysian Journal of Library and Information Science, 2017)
Vimala, V., & Reddy, V. P. (1996). Authorship pattern and collaborative research in the field of zoology. Malaysian Journal of Library & Information Science, Vol.1, no. 2: 43-50 Studies the trend in authorship pattern and collaborative research in zoology with a sample of 19,323 journal citations figured in the theses on zoology accepted for the award of the doctoral degree by Sri Venkateswara University, Tirupati, India. The study indicates that although multiple authorship is dominant, solo research also exists. The proportion of single authored papers has shown a declining trend during the period 1901-1995. It is observed that the proportion of single authorship is likely to be insignificant after the year 2030. The degree of collaboration in research is 0.75 in zoology as a whole.